Actuator Fault and Disturbance Estimation using the T-S fuzzy model. Issue 1 (July 2017) - Li, Shanzhi; Wang, Haoping; Aitouche, Abdel; Tian, Yang; Christov, Nicolai
Abstract: This paper presents an actuator fault and disturbance estimation strategy using Takagi-Sugeno (TS) fuzzy model. In this approach, using a coordinate transformation, the TS fuzzy system is decomposed into three different modules: state subsystem without fault and disturbance, disturbance subsystem without fault, fault subsystem without disturbance. After the transformation, the fault and disturbance can be decoupled and calculated from the input and output signals and estimation state. The convergence of TS fuzzy observer is analyzed and proved. In order to verify the performance of the proposed approach, a wind turbine system with actuator fault and disturbance have been tested, the simulation results illustrate the efficiency of the proposed strategy.